1996
DOI: 10.1111/j.1540-8159.1996.tb03357.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Age, Lead Axis, Frequency of Arrhythmic Episodes, and Atrial Dimensions on P Wave Triggered SAECG in Patients with Lone Paroxysmal Atrial Fibrillation

Abstract: Signal-averaged P wave of 42 patients with lone paroxysmal atrial fibrillation (PAF) and 29 normal subjects (N) were recorded, using three orthogonal leads and analyzed in the time and frequency (entire P wave or a 100-ms segment ranging from 75 ms before to 25 ms after the end of P wave) domains. PAFs were divided into a group of 12 having > or = 2 attacks a month (HF) and a group of 30 having < or = 2 attacks a year (LF). Statistically significant differences were absent with regard to ages of PAF and N; age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 20 publications
1
15
0
4
Order By: Relevance
“…We depicted these trends by comparing the age- and sex-adjusted restricted splines, which showed clear evidence supporting these trends. These observations have been confirmed in other studies employing signal-average ECGs2224 and in reference ranges derived from an international registry 25…”
Section: Discussionsupporting
confidence: 76%
“…We depicted these trends by comparing the age- and sex-adjusted restricted splines, which showed clear evidence supporting these trends. These observations have been confirmed in other studies employing signal-average ECGs2224 and in reference ranges derived from an international registry 25…”
Section: Discussionsupporting
confidence: 76%
“…11 However, age cannot be considered as a predictive parameter for AF recurrence in patients with mitral stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason for these different findings was the frequency range analyzed, since the latter used band-limited signals to 80 -400 Hz, and the former analyzed the frequency range from 0 to 300 Hz. In this sense, Michellucci et al reported that 95% of the energy content of the P-wave in patients with lone AF was concentrated bellow 50 Hz [40]. Barbosa et al [23,38] also adopted the X-modified lead to emphasize P-wave amplitude, as described in the present study.…”
Section: P-wave Signal-averaged Electrocardiogrammentioning
confidence: 87%